Consumer Purchase Intention Post COVID-19 Pandemic Through Marketplace : An Action Learning Study - Ferdiansyah, Oky Arif; Nugroho, Sukmo Hadi (Jurnal Ilmiah Pangabdhi, 2023)
This study aims to find out and complement existing information related to the influence of e-trust, e-satisfaction, and social influence on purchase intention mediated by e-value. This is a survey research that uses quantitative methods with data collection techniques through online questionnaires which were distributed to 700 marketplace consumer respondents who had purchased cell phones or gadgets from January 2023 to June 2023. There were 700 questionnaires distributed and 233 returned, but only 155 were used according to this study’s criteria. This research was carried out through a validity test and a reliability test through the MSA test with the KMO and Bartlett tests. The hypothesis test used SEM-PLS through SmartPLS 3.3.9 software. The results showed that four of the seven hypotheses proposed in this study were proven positive and significant: the effect of e-trust on e-value and purchase intention, the effect of social influence on e-value and purchase intention, while the other hypotheses which could not be proven (not significant) were the effect of e-satisfaction on e-value and purchase intention, and the effect of e-value on purchase intention. In addition, indirectly, e-value plays a role in mediating the effect of e-trust and social influence on purchase intention because it is able to change (weaken) the significant effect to be insignificant. As for mediating the effect of e-satisfaction on purchase intention, the e-value variable is unable to mediate (strengthen) because the results are not significant or the same as the direct effect of e-satisfaction on purchase intention.